Intentional Controlled Islanding in Wide Area Power Systems with Large Scale Renewable Power Generation to Prevent Blackout - Babaei, Mehdi (Curtin University, 2023)
Intentional controlled islanding is a solution to prevent blackouts following a large disturbance. This study focuses on determining island boundaries while maintaining the stability of formed islands and minimising load shedding. A new generator coherency identification framework based on the dynamic coupling of generators and Support Vector Clustering method is proposed to address this challenge. A Mixed Integer Linear Programming model is formulated to minimize power flow disruption and load shedding, and ensure the stability of islanding. The proposed algorithm was validated in 39-bus and 118-bus test systems.